The impact of diversification on the banking industry : a non-stationary panel approach in the presence of cross section dependence - Craigwell, Roland...[et al.] ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
User non-stationary panel techniques along with quarterly data for the Barbadian banking industry between 1979 and 2005 to empirically investigate the link between diversification and commercial bank risk and return.